PROTOTIPE SISTEM PAKAR DENGAN METODE VARIABLE CENTERED INTELLIGENT RULE SYSTEM UNTUK MENDIAGNOSA PENYAKIT PADA ANJING (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2015)
In this research, design and manufacture a prototype of expert system are used to help to determinethe dog diseases. This prototype is intended to provide an access information about type of dog diseasesand therapeutic advice to owner, physician assistants and veterinarians themselves. The prototype of anexpert system is developed using Variable-Centered Intelligent Rule System and certainty factor method.A Variable-Centered Intelligent Rule System method is able to knowledge development, update knowledgeand consultation or process of inference. Certainty factor method itself is used to give consideration tothe weighting process on the symptoms of the disease so that the weighting process has been able toprovide the results of diseases with a value of confidence from the system. The input of developmentknowledge is results of knowledge representation that have been made based on interview with an expertin veterinary. In the knowledge development process each symptoms/variables will be calculated and willgeneralize the symptoms/variables on update knowledge based on its results. In the consultation process,input on expert system is the symptoms of disease which given by user and displayed by system, then theoutput of the system is the diseases based on its answer.The final result of this research is a prototype ofexpert system for diagnosing diseases of the dog and its value of confidence of the disease that indicatesthe level of confidence in the system against the disease therapeutic advice that should be given. Theresult of this research shows that the method of Variable-Centered Intelligent Rule System and certaintyfactor could be implemented in prototype of expert system for diagnosing diseases in dog